2004
DOI: 10.1128/jvi.78.23.12888-12900.2004
|View full text |Cite
|
Sign up to set email alerts
|

Requirement of Sur2 for Efficient Replication of Mouse Adenovirus Type 1

Abstract: Mouse adenovirus type 1 (MAV-1) early region 1A (E1A) encodes a virulence gene in viral infection of mice. To broaden our understanding of the functions of E1A in MAV-1 pathogenesis, an unbiased experimental approach, glutathione S-transferase (GST) pulldown, was used to screen for cellular proteins that interact with E1A protein. We identified mouse Sur2, a subunit of Mediator complex, as a protein that binds to MAV-1 E1A. The interaction between Sur2 and MAV-1 E1A was confirmed in virus-infected cells. Conse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
33
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(39 citation statements)
references
References 64 publications
(81 reference statements)
6
33
0
Order By: Relevance
“…A recent report has shown that murine Sur2 is needed for efficient replication of mouse adenovirus type 1 in mouse embryo fibroblasts (48). Sur2 is a subunit of the transcription mediator complex, which bridges transcription regulators to RNA polymerase II.…”
Section: Discussionmentioning
confidence: 99%
“…A recent report has shown that murine Sur2 is needed for efficient replication of mouse adenovirus type 1 in mouse embryo fibroblasts (48). Sur2 is a subunit of the transcription mediator complex, which bridges transcription regulators to RNA polymerase II.…”
Section: Discussionmentioning
confidence: 99%
“…However, after infection with a single virion, the level of early gene transcription is too low to support viral replication unless E1A CR3 turns up the rate of reinitiation by 5-20-fold, depending on the early viral promoter. Similarly murine adenovirus I, which encodes an E1A with a homolgous CR3 that interacts with murine MED23, requires MED23 for high rate transcription of its early genes at low multiplicity of infection (Fang et al, 2004).…”
Section: E1a Conserved Region 3 Activation Of Early Viral Gene Expresmentioning
confidence: 99%
“…The CR3 regions of several HAdv types have also been reported to bind with MED23 (22). In Med23 KO cells infected with the mouse adenovirus 1 (MAdv 1) (which codes for an E1A protein that contains a CR3 domain related to HAdv5 CR3), the levels of early gene transcription were retarded, suggesting that Med23 plays an important role in the transcriptional activity of MAdv E1A (23). Although MED23 has been shown to promote transcription at the recruitment and postrecruitment steps in transcriptional initiation by EGR 1 (24), the precise role of MED23 in the transcriptional activation of HAdv5 early genes remains to be elucidated.…”
mentioning
confidence: 99%